Do you know Company Value? It's Depend on Accounting Disclosure and Performance Environment: Evidence from Indonesian Country - Saputro, Julianto Agung; Indraswono, Cahyo (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2022)
This research is important to do to find out the factors that affect the firm value. Therefore, researchers want to examine the effect of ADCE and environmental performance on firm value. Researchers used the 2016 GRI standards to measure environmental performance. The results of this study are expected to add/strengthen empirical evidence regarding legitimacy theory and the triple bottom line concept as well as deepen knowledge about what factors can affect firm value, which can be used as additional references for research. in the future and hopes to add to the company's initiatives in preserving the environment. This study provides the following conclusions accounting disclosure Carbon emissions have a negative effect on firm value and environmental performance has a positive effect on firm value. This means that if the environmental performance of a company is getting better, it can increase the value of the company because investors will give a positive response by buying company shares so that it can increase share prices which have implications for increasing company value. For the government, if ADCE is made as a regulation, what must be considered is to provide a third party as a verifier in the calculation of carbon emissions so that the ADCE disclosed by the company can be trusted. For companies, if they want to disclose carbon information voluntarily, it is better to choose which information should be disclosed.